Germany : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2022)
Germany entered COVID-19 with strong public and private sector balance sheets, and large financial buffers. The financial sector has weathered well the shocks related to COVID-19 and the impact of the war has been limited so far. However, financial conditions have tightened recently and risks to the economy and the financial system have increased. The main risks relate to an escalation of the war that could be associated with a Russian gas shut off and higher commodity prices, a global resurgence of COVID-19 with extended supply chain disruptions, and de-anchoring of inflation expectations in the U.S. and advanced Europe. Structural vulnerabilities related to persistent low bank profitability and misalignments in the real estate sector prices indicated in the 2016 FSAP remain a concern.